Investigating the situation and analyzing the dimensions of superstitions of football and futsal athletes in Kerman - Elham Sadat Hosseini Moghadam; Hossein Poursoltani Zarandi; Reza Shaji (Islamic Azad university, Isfahan Branch, 2022)
Objective: Despite the advances in science and technology and the dominance of knowledge over human society, superstitious beliefs and behaviors still operate in different societies. Sport is one of the areas that is no exception. The tendency to superstition is a defense mechanism that arises as a result of not believing in one's abilities, the tendency to control and certainty in the future. The purpose of this study is to analyze the dimensions of superstitions in football and futsal athletes in Kerman.Methodology: The research method in terms of type and data analysis is quantitative and field survey. The statistical population of the study consists of 200 football and futsal players in Kerman, which were selected by the stratified sampling method.Results: The results of this study show that among the various dimensions of superstitious behaviors, the individual, psychological, belief and environmental dimensions have the greatest impact on creating belief and, consequently, superstitious behaviors among the athletes of Kerman.Conclusion: The dimensions of superstition are affected by different degrees of influence on athletes which are due to individual differences between research samples.